Defense Industrial Base and Armed Forces: potentialities and challenges in the context of the Defense Economy - Gonçalves da Silva, Marcus Vinicius (2023)
In Brazil, the consolidation of an Industrial Defense Base (IDB) composed of state and private, civil and military companies, focused on the development of Strategic Defense Products (SDE), goes through constant challenges, such as the irregular allocation of budgetary resources destined to the Armed Forces. Studies have shown the importance of the defense sector for industrial development, pointing out that innovations in the sector generate technological spillovers for the growth of the national economy. The methodology used is a case study, as this article analyzes the current context of the Armed Forces and the IDB and the phenomena that influence them from the perspective of the defense market-budget binomial.